A survey for selected avian viral pathogens in backyard chicken farms in Finland. Issue 2 (4th March 2017) - Pohjola, L.; Tammiranta, N.; Ek-Kommonen, C.; Soveri, T.; Hänninen, M. L.; Fredriksson Ahomaa, M.; Huovilainen, A.
ABSTRACT: Backyard poultry are regaining popularity in Europe and increased interest in the health and management of non-commercial farms has resulted. Furthermore, commercial poultry farm owners have become concerned about the risk represented by contagious avian diseases that nearby backyard poultry could transmit. Fifty-one voluntary backyard chicken farms were visited between October 2012 and January 2013. Blood samples and individual cloacal swabs were collected from 457 chickens. In 44 farms (86%), one or more of the tested chickens had antibodies against avian encephalomyelitis and chicken infectious anaemia viruses, 24 farms (47%) had chickens seropositive for infectious bronchitis virus, 10 farms (20%) had chickens seropositive for infectious bursal disease virus, six farms (12%) had chickens seropositive for infectious laryngotracheitis virus and two farms (5.4%) had chickens seropositive for avian influenza virus. No farms had chickens seropositive for Newcastle disease virus. Of the 51 farms, five (10%) had chickens positive for coronavirus reverse transcription polymerase chain reaction. A phylogenetic analysis showed that all backyard chicken coronaviruses collected were QX type infectious bronchitis viruses. All chickens tested for avian influenza and Newcastle disease viruses using real time reverse transcription polymerase chain reaction were negative. To our knowledge, there is no evidence to date to suggest that these diseases would have been transmitted between commercial and non-commercial flocks.